Regularities in Fullerene C60 Fragmentation According to Laser-Desorption Mass-Spectrometric and Quantum Chemical Data - Karpenko, A.B.; Kuts, V.S.; Snegir, S.V.; Pokrovskiy, V.A. (Ukrainian Journal of Physics, 2012)
Experimental and theoretical results concerning the regularities in the fullerene C60 fragmentation are reported. The destruction of C60 thermally deposited onto a silicon substrate is studied with the use of laser-desorption mass spectrometry and provided various values of laser radiation power. The intensity of [C60]+ ions in the mass spectrum is shown to increase linearly, when the laser radiation power grows from 30 to 70% of its maximum. At the same time, the relative degree of C60 fragmentation first increases and then saturates at 50% of the laser power maximum. Two possible mechanisms of fullerene ionization are proposed. The electron structures of molecular, C60–2n, and cationic, [C60–2n]+, fullerene forms, where the parameter n = 0 to 4 indicates the number of lost C2 fragments, are calculated within the quantum chemistry method. The boundary molecular orbitals (EHOMO and ELUMO), adiabatic ionization potentials, and electron affinities are calculated.